Enzyme‐Inspired Microenvironment Engineering of a Single‐Molecular Heterojunction for Promoting Concerted Electrochemical CO2 Reduction - Han, Shu‐Guo; Zhang, Min; Fu, Zhi‐Hua; Zheng, Lirong; Ma, Dong‐Dong; Wu, Xin‐Tao; Zhu, Qi‐Long (Advanced materials (Weinheim), 2022)
Challenges remain in the development of novel multifunctional electrocatalysts and their industrial operation on low‐electricity pair‐electrocatalysis platforms for the carbon cycle. Herein, an enzyme‐inspired single‐molecular heterojunction electrocatalyst ((NHx)16‐NiPc/CNTs) with specific atomic nickel centers and amino‐rich local microenvironments for industrial‐level electrochemical CO2 reduction reaction (eCO2RR) and further energy‐saving integrated CO2 electrolysis is designed and developed. (NHx)16‐NiPc/CNTs exhibit unprecedented catalytic performance with industry‐compatible current densities, ≈100% Faradaic efficiency and remarkable stability for CO2‐to‐CO conversion, outperforming most reported catalysts. In addition to the enhanced CO2 capture by chemisorption, the sturdy deuterium kinetic isotope effect and proton inventory studies sufficiently reveal that such distinctive local microenvironments provide an effective proton ferry effect for improving local alkalinity and proton transfer and creating local interactions to stabilize the intermediate, ultimately enabling the high‐efficiency operation of eCO2RR. Further, by using (NHx)16‐NiPc/CNTs as a bifunctional electrocatalyst in a flow cell, a low‐electricity overall CO2 electrolysis system coupling cathodic eCO2RR with anodic oxidation reaction is developed to achieve concurrent feed gas production and sulfur recovery, simultaneously decreasing the energy input. This work paves the new way in exploring molecular electrocatalysts and electrolysis systems with techno‐economic feasibility. An enzyme‐inspired single‐molecular heterojunction electrocatalyst with accurate amino‐rich microenvironments around the active sites is uniquely designed to enable efficient CO2 capture and fast proton ferrying during CO2 electroreduction, which achieves concurrent CO production at the cathode and sulfur recovery at the anode with industrial‐level current density and lower energy consumption.